GREENING UZBEKISTAN: STRATEGIES FOR A SUSTAINABLE FUTURE - Rixsievna, Shayusupova Lobar; Ugli, Khasanov Azizjon Akhro (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
: This article examines the critical need for Uzbekistan to expedite its transition to a green economy. The research highlights the severe risks posed by delaying this transition, including significant economic losses from land degradation and dust storms, high carbon and energy intensity, and the potential lock-in of outdated technologies. Uzbekistan's government has already initiated the "Strategy for the Transition to a Green Economy (2019–2030)," aiming to diversify energy sources, improve resource efficiency, and adapt to climate change impacts. Additionally, the Ministry of Economic Development and Poverty Reduction is developing a Green Growth Strategic Framework to further these efforts. The article also emphasizes the importance of mobilizing both public and private investments to meet the financial demands of sustainable development and align with international climate commitments.